SMARCA4 loss is synthetic lethal with CDK4/6 inhibition in non-small cell lung cancer - Yibo Xue (Nature Portfolio, 2019)
Non-small cell lung cancers with inactivating SMARCA4 mutations are currently undruggable. Here, the authors show that the absence of SMARCA4/2 reduces chromatin accessibility at the CCND1 locus, leading to a subsequent reduction in cyclin D1 expression, which promotes vulnerability of these cancers to CDK4/6 inhibition.